KEMAMPUAN BAKTERI DIAZOTROF ENDOFIT UNTUK MENINGKATKAN PERTUMBUHAN VEGETATIF BIBIT KELAPA SAWIT (Elaeis guineensis jacq) - Andreas Panjaitan; Iswandi Anas; Rahayu Widyastuti; Wiwik Eko Widayati (Jurnal Ilmu Tanah dan Lingkungan, 2015)
Endophytic diazotrophic bacteria are free-living atmospheric dinitrogen fixing bacteria that lived and colonized between living plant cells and do not contribute pathogenic effects to its host. The ability of endophytic diazotrophic bacteria in providing nitrogen as a nutrient for crop plays an important role in reducing the dependency of inorganic nitrogen fertilizer. The aim of this experiment was to study the ability of endophytic diazotrophic bacteria isolate to stimulate vegetative growth of oil palm seedlings at four levels inorganic nitrogen fertilizer application. Experiment was conducted at the greenhouse IPB Campus, Cikabayan, Darmaga with the altitude of 250 m above sea level and at the Soil Fertility Laboratory, the Departement of Soil Science and Land Resources, Faculty of Agriculture, Bogor Agricultural University (IPB) and at the Laboratory of Biotechnology, Indonesian Sugarcane Research Centre (P3GI) Pasuruan, East Java. This experiment using Completely Randomized Block Design (CRBD) consisted of two factors with three replications. The first factor was inorganic nitrogen levels consisted of four levels (0, 50%, 75% and 100% of the recommended dose). The second factor was inoculation with endophytic diazotrophic bacterial isolates consisted of four levels; without inoculation, inoculated with isolate 1, isolate 2 and isolate 3. The results of the experiment showed that the inoculation with bacterial isolate 2 without N fertilizer application gave the best results to increase the diameter of the palm weevil, palm height, and dry weight. In addition to that, the application of endophytic diazotrophic bacterial isolate was able to promote vegetative growth of palm oil seedling. Keywords: Endophytic diazotrophic bacteria, nutrient up-take, oil palm seedling, vegetative growth